Bacterial abundance and pH associate with eDNA degradation in water from various aquatic ecosystems in a laboratory setting - Zhao, Beilun; van Bodegom, Peter M.; Trimbos, Krijn Baptist (Frontiers in Environmental Science, 2023)
Environmental DNA (eDNA) has been widely used in biomonitoring and has major advantages compared to traditional methods such as counting observations. However, the persistence of eDNA within an ecosystem can lead to false-positive results on the presence of organisms. To improve the accuracy of the interpretation of eDNA results, the present study aimed to enhance the understanding of the connection between environmental factors and eDNA persistence. Here, we set up tank experiments using freshwater from 16 field locations involving four ecosystem types and Milli-Q water as control to cultivate zebrafish, and monitor eDNA degradation over time after removing the organisms. Bacterial abundance, nitrate, phosphate, dissolved oxygen and pH were analyzed to evaluate their impacts on eDNA degradation. We found that bacterial abundance and pH were positively related to eDNA degradation. The eDNA at the size range of 1.2-5 μm (extracellular but intro-mitochondrial) decreased faster than at the >5 μm (intracellular) size range, leading to changes in the eDNA particle size proportion (PSP) with degradation. eDNA PSP in the field water was different from in Milli-Q water. In conclusion, our findings help understand how eDNA persistence is connected with both abiotic and biotic environmental factors, and thereby will improve the accuracy of eDNA methods in aquatic biomonitoring.